Do concurso formal de crimes - Felipe Machado Prates (2015)
The present work begins by identifying a theory from Concursus normarum in Criminal Law Scoping ideal and real concurrence of offences, continuing offences and apparent concurrence -, ruled by the material non bis in idem and full appraisal principles. Ideal concurrence of offences, in this context, is considered an intermediate figure between the real concurrence of offenses and apparent concurrence of norms, considering the form of valuation of the fact through applicable norms. Those premisses considered, there follows a general perspective of ideal concurrence of offences, with reference to its historical progress and tradicional assumptions, consequences, fundaments, law nature and conceptual peculiarities. Following that, a thorough examination of each of the specific assumptions in real concurrence of offences, starting by the most controversial assumption, the definition of the unity of action concept. The second assumption, of plurality of crimes, is defined by the tatbestandliche Handlungseinheit theory, still of incipient use in Brazil. Besides those two assumptions traditionally related to ideal concurrence, the one about the inexistence of apparent concurse of criminal norms is also considered. After analysing these assumptions, the autonomous purposes concept is defined, considering its role in differentiating the proper and improper ideal concurrence and the fact its rarely analysed by the national doctrine. The punishment criterions used in national and foreign law are also analysed in its role of setting penalties in ideal concurrence of offences, highliting the positive and negative aspects of each. And so, the doctrines criticism regarding the crimes concurrence separation between ideal and real concurrence and its adoption in foreigner law.